Changes in functional connectivity of the brain associated with a history of sport concussion: A preliminary investigation. (2nd January 2017) - Churchill, Nathan; Hutchison, Michael G.; Leung, General; Graham, Simon; Schweizer, Tom A.
ABSTRACT: Objective : There is evidence of long-term clinical consequences associated with a history of sport concussion. However, there remains limited information about the underlying changes in brain function. The goal of this study was to identify brain regions where abnormal resting-state function is associated with chronic concussion, for athletes without persistent symptoms. Methods : Functional Magnetic Resonance Imaging (fMRI) was performed on a group of athletes with prior concussion ( n = 22) and a group without documented injury ( n = 21). Multivariate predictive modelling was used to localize reliable changes in brain connectivity that are associated with a history of concussion and with clinical factors, including number of prior concussions and recovery time from last injury. Results : No significant differences were found between athletes with and without a history of concussion, but functional connectivity was significantly associated with clinical history. The number of prior concussions was associated with most extensive connectivity changes, particularly for elements of the visual attention network and cerebellum. Conclusion : The findings of this preliminary study indicate that functional brain abnormalities associated with chronic concussion may be significantly dependent on clinical history. In addition, elements of the visual and cerebellar systems may be most sensitive to the long-term effects of sport concussion.